An urban biorefinery for food waste and biological sludge conversion into polyhydroxyalkanoates and biogas. (1st March 2020) - Moretto, Giulia; Russo, Ivan; Bolzonella, David; Pavan, Paolo; Majone, Mauro; Valentino, Francesco
Abstract: This study focuses on the application of the concept of circular economy, with the creation of added-value marketable products and energy from organic waste while minimizing environmental impacts. Within this purpose, an urban biorefinery technology chain has been developed at pilot scale in the territorial context of the Treviso municipality (northeast Italy) for the production of biopolymers (polyhydroxyalkanoates, PHAs) and biogas from waste of urban origin. The piloting system (100–380 L) comprised the following units: a) acidogenic fermentation of the organic fraction of municipal solid waste (OFMSW) and biological sludge; b) two solid/liquid separation steps consisting of a coaxial centrifuge and a tubular membrane (0.2 μm porosity); c) a Sequencing Batch Reactor (SBR) for aerobic PHA-storing biomass production; d) aerobic fed-batch PHA accumulation reactor and e) Anaerobic co-digestion (ACoD). The thermal pre-treatment (72 °C, 48 h) of the feedstock enhanced the solubilization of the organic matter, which was converted into volatile fatty acids (VFAs) in batch mode under mesophilic fermentation conditions (37 °C). The VFA content increased up to 30 ± 3 g COD/L (overall yield 0.65 ± 0.04 g CODVFA /g VS(0) ), with high CODVFA /CODSOL (0.86 ± 0.05). The high CODVFA /CODSOL ratio enhanced the PHA-storing biomass selection in the SBR by limiting the growth of the non-storing microbial population. Under fully aerobic feast-famine regime, the selection reactor was continuously operated for 6 months at an average organic loading rate (OLR) of 4.4 ± 0.6 g COD/L d and hydraulic retention time (HRT) of 1 day (equal to SRT). The ACoD process (HRT 15 days, OLR 3.0–3.5 kg VS/m 3 d) allowed to recover the residual solid-rich overflows generated by the two solid/liquid separation units with the production of biogas (SGP 0.44–0.51 m 3 /kg VS) and digestate. An overall yield of 7.6% wt PHA/VS(0) has been estimated from the mass balance. In addition, a preliminary insight into potential social acceptance and barriers regarding organic waste-derived products was obtained. Graphical abstract: Image 1 Highlights: Multiple by-products (biopolymer and biogas) from a single urban biorefinery. Feedstock thermal pre-treatment enhanced its the acidification process. Mesophilic anaerobic co-digestion ensured a positive process thermal balance. Overall yield of 7.6% biopolymer mass on the initial volatile solids was estimated. Social survey indicated bin bags derived from organic waste as preferred product.